Concentrated slurry formation via drawdown and incorporation of wettable solids in a mechanically agitated vessel. Issue 5 (23rd February 2018) - Wood, Thomas; Simmons, Mark J. H.; Greenwood, Richard W.; Stitt, E. Hugh
Abstract : This article describes the effect of vessel configurations on the drawdown and incorporation of floating solids to prepare concentrated alumina slurries in stirred tanks. The impeller speed and power draw required to incorporate all dry powder within four seconds, NJI and PJI, are used to evaluate incorporation performance. The effect of impeller type is assessed, with pitched blade impellers proving to be the most effective across the full range of solid contents considered. At higher solids content the energy demand is shown to increase dramatically, with a 100‐fold increase in energy required to add 1% w/w more solid at 50% by weight compared to 1% by weight. Analysis of impeller power numbers show this coincides with a transition from constant power number to a region where power number increases linearly with decreasing Reynolds number. Contrary to studies at low solids content, the presence of baffles is shown to inhibit drawdown. © 2018 The Authors AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers AIChE J, 64: 1885–1895, 2018